Daily life in ancient Rome - Dupont, Florence (Malden, MA [etc.] : Blackwell, 1994)
This book concerns the everyday private and public lives of the citizens of ancient Rome. Drawing on a broad selection of contemporary sources, the author examines the institutions, actions and rituals of day to day life.
2 Wealth and poverty
Prijevod djela: Vie quotidienne du citoyen romain sous la République
Str. [297]-298: Bibliografija
Kazalo
Keywords: antički Rim; Rim -- društveni život -- običaji